الأقوال التي ذمها الله في القرآن الكريم: دراسة في ضوء سورة الحجرات: The Statements Condemned by Allah in the Holy Qur’an: A Study in Light of Sūrah al-Ḥujurāt - حفصة محمود غازي (الدراسات الإسلامية, 2024)
The purpose of this study is to recognise speech behaviours that Allah Almighty has condemned, their damage and harmfulness to society, and the reasons behind their condemnation in the Holy Qur’an, especially in Sūrah al-Ḥujurāt. The method of this research is inductive and analytical. The impermissible sayings have been gathered from the entire Sūrah, divided into different types, and then a detailed discussion of each speech type has been conducted by analysing the verse that discusses it, explaining the Holy Qur’an’s style in censuring it, and detailing the harm it causes to society. This study refers to the great attention that the Holy Qur’an pays towards spreading love and brotherhood in Muslim society, as well as the prohibition of everything that leads to grudge, hatred, and severed ties. The study also discusses the exceptions and special circumstances in which Allah Almighty has allowed these sayings. This research promotes the practicality of the Qur’anic impositions and discusses the allowances within those orders. The research sheds light on the application of the rules of communication in the light of the Holy Qur’an, apropos the current era.